Framing care-giving work for the elderly in Spanish public policy: Gender, power and social justice. (Construcciones políticas en torno al trabajo de cuidados de personas mayores dependientes en España. Género, poder y justicia social) - Elin Peterson (Revista Española de Ciencia Política, 2015)
The ‘care crisis’ has been a recurrent theme in feminist debates and academic studies on care, social policy and citizenship. The care deficit is particularly severe is the ageing societies of Southern Europe. In Spain, familialism prevails in eldercare. This implies a permanent trust on the family, on its intergenerational solidarity and on its gender structure as provider of help and support. At the same time, studies show that migrant domestic workers increasingly meet the care needs of older dependent people. The globalization of care tends to perpetuate the gendered nature of care since the caring tasks remain in women’s hands. Scrutinizing eldercare policies is an important issue for feminist and social policy research given the dominance of women in care-giving and care work and the gendered coding of care work. By means a discourse-oriented policy analysis this paper examines key policy texts related to the reforms of Dependent Care and of Household Employment. The article demonstrates that public policy has an important role in constructing care work(ers); public policy shapes the positions of those doing care-giving work, the valuation of their work, and their social citizenship status. As such, they vitally shape gendered power relations. While family carers and domestic workers are constructed very differently, in common for these two categories of carers is that they perform undervalued work. The findings are discussed in the light of the theoretical conceptualization of recognition and its links to redistribution.